Die Oxypoda-Arten der Kanarischen Inseln: Taxonomie, Bionomie, Phylogenie und Biogeographie (Coleoptera: Staphylinidae, Aleocharinae). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1996)
The Oxypoda species of the Canary Islands are revised. Among the Canarian Staphylinidae, Oxypoda containing 4 widespread and 18 endemic species is the genus with the highest number of species. Two subgenera, Canaroxypoda subg. n. (type species: Oxypoda palmensis sp. n.) and Atlantoxypoda subg. n. (type species: Oxypoda assingi sp. n.), and the following 14 species are described as new: Oxypoda (Baeoglena) gillerforsi sp. n. [La Gomera], Oxypoda (Baeoglena) wunderlei sp. n. [La Gomera], Oxypoda (Baeoglena) tenoensis sp. n. [Tenerife: Teno], Oxypoda (Baeoglena) hernandezi sp. n. [Tenerife: Anaga], Oxypoda (Baeoglena) meybohmi sp. n. [Tenerife: Anaga], Oxypoda (Canaroxypoda) canariensis sp. n. [Gran Canaria], Oxypoda (Canaroxypoda) tenerifensis sp. n. [Tenerife], Oxypoda (Canaroxypoda) gomerensis sp. n. [La Gomera], Oxypoda (Canaroxypoda) hierroensis sp. n. [El Hierro]; Oxypoda (Canaroxypoda) palmensis sp. n. [La Palma], Oxypoda (Atlantoxypoda) piniphila sp. n. [Tenerife], Oxypoda (Atlantoxypoda) silosensis sp. n. [Tenerife: Teno], Oxypoda (Atlantoxypoda) assingi sp. n. [Tenerife: Anaga], and Oxypoda (Atlantoxypoda) ductifera sp. n. [La Palma]. Four further endemic species are redescribed: Oxypoda (Baeoglena) brevipennis Wollaston, 1864 [Tenerife: Anaga]; Oxypoda (Atlantoxypoda) obscoena Wollaston, 1865 [Tenerife]; Oxypoda (Atlantoxypoda) teydensis (Palm, 1975) [Tenerife], and Oxypoda (Atlantoxypoda) aranensis (Israelson, 1985) comb. n. [La Gomera]. Of the widespread species, Oxypoda (Deropoda) arabs Fauvel, 1904 and Oxypoda (Atlantoxypoda) lurida Wollaston, 1857 are redescribed. The Canarian localities for Oxypoda (Podoxya) carbonaria (Heer, 1841) and Oxypoda (Demosoma) haemorrhoa (Mannerheim, 1831) are reported, and a synopsis of their general distribution is given. The presence of Oxypoda exoleta Erichson, 1840 remains doubtful. Oxypoda pierrei Jarrige, 1956 syn. n. is a new synonym of Oxypoda (Deropoda) arabs Fauvel, 1904. Lectotypes are designated for Oxypoda (Deropoda) arabs Fauvel, 1904, Oxypoda (Baeoglena) brevipennis Wollaston, 1864, and Oxypoda (Atlantoxypoda) lurida Wollaston, 1857.For the endemic species as well as for arabs and lurida the genitalia and, if sclerotized, the ventral plates of the last female segment are figured; for lurida, palmensis, and assingi also the mouthparts are illustrated. For 4 species drawings of their habitus are presented. All records are mapped. A diagnostic key to the species is provided. - For each of the endemic Canarian taxa of Oxypoda phylogenetic systems are proposed. Difficulties during the phylogenetic reconstructions result from the lack of material in some species. The endemic Oxypoda represent 3 monophyletic taxa: one species group of the subgenus Baeoglena with 6 species, the subgenus Canaroxypoda with 5 species, and a species group of the subgenus Atlantoxypoda with 7 species. The widespread Oxypoda lurida is probably the sister species of the endemic Atlantoxypoda species.Most species of Oxypoda are stenoecious inhabitants of the laurel woods. However, both an altitudinal differenciation and a preference for certain substrates are observed. All endemic Oxypoda species are island endemics or local endemics of the western islands. - The evolution of 18 endemic species can be explained by 3 colonisation events. The stem species probably came from the Western Palaearctic. - The closest faunal relationships within the archipelago exist between the Teno mountain range of Tenerife and its neighbouring island La Gomera. There is no close relationship to the Oxypoda species of Madeira. - The Oxypoda fauna of the Canary Islands is a typical island fauna. It is characterized by richness in endemic species (82%) and it is, at the same time, accidental.The protection of laurel woods is essential for the preservation of the endemic Oxypoda species.KeywordsCanary Islands, Oxypoda, new subgenera, new species, designation of lectotypes, identification key, phylogenetic reconstructions, altitudinal differenciation, substrate preference, island endemics and local endemics, island fauna, importance and protection of laurel woods.Nomenclatural ActsAtlantoxypoda Zerche, 1996 (Oxypoda), sgen. n.Canaroxypoda Zerche, 1996 (Oxypoda), sgen. n.pierrei Jarigge, 1956 (Oxypoda), syn. n. of Oxypoda (Deropoda) arabs (Fauvel, 1904)aranensis (Israelson, 1985) (Oxypoda (Atlantoxypoda)), comb. n. hiterto Geostiba aranensisassingi Zerche, 1996 (Oxypoda (Atlantoxypoda)), spec. n.ductifera Zerche, 1996 (Oxypoda (Atlantoxypoda)), spec. n.lurida Wollaston, 1857 (Oxypoda (Atlantoxypoda)), Lectotypepiniphila Zerche, 1996 (Oxypoda (Atlantoxypoda)), spec. n.silosensis Zerche, 1996 (Oxypoda (Atlantoxypoda)), spec. n.brevipennis Wollaston, 1864 (Oxypoda (Baeoglena)), Lectotypegillerforsi Zerche, 1996 (Oxypoda (Baeoglena)), spec. n.hernandezi Zerche, 1996 (Oxypoda (Baeoglena)), spec. n.meybohmi Zerche, 1996 (Oxypoda (Baeoglena)), spec. n.tenoensis Zerche, 1996 (Oxypoda (Baeoglena)), spec. n.wunderlei Zerche, 1996 (Oxypoda (Baeoglena)), spec. n.canariensis Zerche, 1996 (Oxypoda (Canaroxypoda)), spec. n.gomerensis Zerche, 1996 (Oxypoda (Canaroxypoda)), spec. n.hierroensis Zerche, 1996 (Oxypoda (Canaroxypoda)), spec. n.palmensis Zerche, 1996 (Oxypoda (Canaroxypoda)), spec. n.tenerifensis Zerche, 1996 (Oxypoda (Canaroxypoda)), spec. n.arabs (Fauvel, 1904) (Oxypoda (Deropoda)), Lectotype described as Oxypoda arabs